Edukasi Pemanfaatan Serum Hemolisis dengan Penambahan Anti-Rh pada Petugas Laboratorium Puskesmas Mekar Sari - Bastian; Firna Kamilatun Nuha; Juwy Trianes; Indah Sari (LPPM STIKES Guna Bangsa Yogyakarta, 2022)
Clinical laboratory examination is a system that can determine decisions regarding a disease diagnosis or monitoring of healing through laboratory results. The stages of laboratory quality control are divided into three stages, namely pre-analytic, analytical, and post-analytic stages. The biggest error in taking blood specimens in the pre-analytic stage is the occurrence of hemolysis among other cases. Hemolysis serum can be reprocessed with the addition of anti-Rh reagent so that it can be used in laboratory examinations. As an effort to answer the problems faced by laboratory workers at Mekar Sari Health Center regarding the use of hemolysis serum, it is necessary to carry out socialization and education so as to increase knowledge and understanding of Mekar Sari laboratory workers. Explanation of material regarding the use of hemolysis serum with the addition of anti-Rh through poster media, and demonstrating the end of the activity.